2019
DOI: 10.3390/cells8060557
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Bioactive Peptides in Invasive Sea Grass Halophila stipulacea

Abstract: Halophila stipulacea is a well-known invasive marine sea grass in the Mediterranean Sea. Having been introduced into the Mediterranean Sea via the Suez Channel, it is considered a Lessepsian migrant. Although, unlike other invasive marine seaweeds, it has not demonstrated serious negative impacts on indigenous species, it does have remarkable invasive properties. The present in-silico study reveals the biotechnological features of H. stipulacea by showing bioactive peptides from its rubisc/o protein. These are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…If they are not available, peptides are not taken into account. Simulation of proteolysis using the BIOPEP-UWM database has recently been described by, e.g., Lin et al [85], Yu D. et al [91], and Kandemir-Cavas et al [92]. Data concerning proteolysis simulation may be interpreted together with protein structures [93].…”
Section: Discussionmentioning
confidence: 99%
“…If they are not available, peptides are not taken into account. Simulation of proteolysis using the BIOPEP-UWM database has recently been described by, e.g., Lin et al [85], Yu D. et al [91], and Kandemir-Cavas et al [92]. Data concerning proteolysis simulation may be interpreted together with protein structures [93].…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive peptides are obtained via wet lab studies. The bioinformatic tools are also used for discovering of bioactive peptides (Agirbasli & Cavas, 2017;Kandemir-Cavas et al, 2019). In this study, Pvtoxin-a and Pvtoxin-b from P. volitans were studied as model proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Also, peptides with this length have a higher resistance to degradation, increasing their bioavailability and, more significantly, bioactivity (52). It has been reported that the determination of binding energy based on in silico experimental methods using HPEPDOCK shows a good correlation with the results obtained experimentally so that these molecules are the ones with the higher antiadipogenic potentiality (53,54). However, concerning the results obtained with Autodock tools, the peptides TTPW, ATSF, ITY, and TSF showed the formation of hydrogen bonds in anti-adipogenic regions of the PPARγ receptor, mainly the three presented bonds with Cys285, which has been since it presents more significant antiadipogenic effects, with binding energies of −5.96, 3.89, −5.91, and −4.68 kcal/mol, respectively (28).…”
Section: In Silico Methodologymentioning
confidence: 97%